2010
DOI: 10.1186/1471-227x-10-13
|View full text |Cite
|
Sign up to set email alerts
|

Fatal poisonings in Oslo: a one-year observational study

Abstract: BackgroundAcute poisonings are common and are treated at different levels of the health care system. Since most fatal poisonings occur outside hospital, these must be included when studying characteristics of such deaths. The pattern of toxic agents differs between fatal and non-fatal poisonings. By including all poisoning episodes, cause-fatality rates can be calculated.MethodsFatal and non-fatal acute poisonings in subjects aged ≥16 years in Oslo (428 198 inhabitants) were included consecutively in an observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 30 publications
(43 reference statements)
2
25
0
1
Order By: Relevance
“…The studies done in various developed countries are showing that deaths are more frequently with pharmaceutical drugs like narcotic opioids and carbon monoxide as evident, China, 24 USA, 18 New Zealand, 23 Turkey 5 and Norway. 22 The Asian studies (Turkey, 25 Korea, 3 Jordan 26 and China 6 ) have demonstrated that a greater number of people are affected with agriculture related poisons as these countries are agro dominant. Bulgaria 16 and Uganda 27 have shown the highest number of deaths due to alcohol.…”
Section: Discussionmentioning
confidence: 98%
“…The studies done in various developed countries are showing that deaths are more frequently with pharmaceutical drugs like narcotic opioids and carbon monoxide as evident, China, 24 USA, 18 New Zealand, 23 Turkey 5 and Norway. 22 The Asian studies (Turkey, 25 Korea, 3 Jordan 26 and China 6 ) have demonstrated that a greater number of people are affected with agriculture related poisons as these countries are agro dominant. Bulgaria 16 and Uganda 27 have shown the highest number of deaths due to alcohol.…”
Section: Discussionmentioning
confidence: 98%
“…Correct identification of cause may be difficult, but it is of great concern when it comes to strategies for prevention. [10][11][12] The deaths caused by drugs of abuse are often referred to as ''overdoses.'' Most of these deaths are now classified as accidents.…”
Section: Discussionmentioning
confidence: 99%
“…Annual mortality rate due to acute poisonings in Oslo has been reported as 24 per 100,000 inhabitants (Bjornaas et al 2010b). In the same study, the percentage of deaths per acute poisoning episode was 3% and the leading toxic agents were opiates or opioids (65% of cases) followed by ethanol (9%), tricyclic anti-depressants (4%), benzodiazepines (4%), and zopiclone (4%).…”
Section: Discussionmentioning
confidence: 99%